Penerapan Eco-Green Pada Bangunan Gedung Sarana Olahraga Kabupaten Garut - Mirza Fathir; Anjas Ninda Hantari; Rendi Rendi; Syamsan Abdullah (Jurnal Konstruksi, 2024)
This research aims to evaluate and analyze the application of the Eco-Green concept in sports facilities buildings in Garut Regency. Eco-Green is a design and construction approach that aims to reduce the environmental impact of buildings, by paying attention to energy efficiency, the use of environmentally friendly materials and waste management. Garut Regency as a research location was chosen because of the need to develop sustainable infrastructure. This research method includes field surveys, documentation analysis, and interviews with relevant stakeholders. The data obtained was used to evaluate the implementation of the Eco-Green concept in sports facilities buildings in Garut Regency. It is hoped that the results of this research will provide a comprehensive view of the successes and challenges in implementing Eco-Green principles in the context of sports infrastructure development in this region. This research contributes to the practical understanding of the implementation of Eco-Green in sports facilities and identifies critical factors that influence the successful implementation of this concept. The implications of the results of this research can be a basis for decision makers in the field of infrastructure planning and development, especially in the context of sustainable development. Apart from that, this research can also be a reference for further research on the development of the Eco-Green concept in the building and infrastructure construction sector in other areas.